Short communication. Telluric pathogens isolated from bean plants with collar and root rots in northwest Spain - Andres Ares, J.L.=700 1 Rivera Martinez, A.; Pomar Barbeito, F.
(Es, En)
ilus., 36 ref.
Keywords: FUSARIUM SOLANI; RHIZOCTONIA SOLANI; PYTIUM; ENFERMEDADES FUNGOSAS; PHASEOLUS VULGARIS; ESPAÑA